PENGARUH INVESTMENT OPPORTUNITY SET (IOS) DAN MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA). - Fitri, Fitri Ratnasari B1021131075 (Jurnal Manajemen Update, 2018)
This study aims to determine the effect of Investment Opportunity Set (IOS) and Corporate Governance mechanisme which includes Independent Board Of Commissioner, Institutional Ownership, Managerial Ownership on  firm value a proxid by Tobin’s Q.  Employing the purposive sampling methode, total sample utilized 25 manufacturing a companies consists of listed on the indonesia stock exchange for the period 2011-2015. Their study is using panel data with the number of observation is 125 form years data. Collected data is the analyzed by employing the multiple regression analyzed. The results of this study show that (1) Investment Opportunity Set (IOS) have a significant positive effect on the value of the company. (2) The mechanisme of Corporate Governance which is proxied by Independent Board Of Commissioner and Institusional Owners has a significant negative effect to firm value, while Managerial Ownership has a significant positive effect to for value.. Keywords : Investment Opportunity Set (IOS) and Corporate Governance mechanisms proxied with Independent Board Of Commissioners, Institutional Ownership and Managerial Ownesrship